Increasing The Performance of Public Health Centers: Does Accountability Role as Moderating? - Basri, Yesi; Azhar A, Al; Lestari, Hesti (Jurnal AKSI (Akuntansi dan Sistem Informasi), 2024)
By assessing the effectiveness of human resources and internal control as independent variables and accountability as moderating variables, this study attempts to investigate the elements that affect the performance of public health institutions.. The population in this study were all public health centers in the city of Pekanbaru; as many as 20 health centers were used as samples in this study. The research method was carried out with a survey conducted in February-March 2021. There were 120 respondents in this survey, including the Head of the PublicHealth Center, the Head of Administration, the Treasurer of Expenses, the Treasurer of Receipts, the Personnel Division, and the Service Sector. The results of numerous analyses show that accountability enhances the public health center's effectiveness and has a favorable influence on the standard of internal control and human resources. This study has consequences for public sector organizations in terms of performance evaluation and motivational content by raising the standard of internal control, accountability, and human resources